Politics of Law of Employment on the Organization of Jobs for Persons with Disabilities - Rhema Kristiono; A. Uwiyono (Budapest International Research and Critics University, 2022)
Indonesia is a country that upholds human rights, the protection of human rights is an obligation for the Government of Indonesia. This protection is also provided for persons with physical disabilities. Indonesia already has a set of laws that provide protection regarding the right to work for persons with disabilities, in this case the Government has an obligation to fulfill the rights of persons with disabilities in particular to get a job. Law No. 8 of 2016 concerning Persons with Disabilities Article 11 letter (g) states to have the opportunity to develop a career path and all the normative rights inherent in it. However, in reality Indonesia still faces problems in fulfilling the right to work for persons with disabilities. The method used in this research is normative juridical in which the data is collected by examining library research in the form of books, journals, and legislation. The purpose of this research is to find out the fulfillment of the right to work for persons with disabilities and the challenges they face in getting a job. Legal Politics used in analyzing this research are Legal Politics by Satjipto Rahardjo and Model Corporate Policy Practices in Labor Law by Tamara Lothion. The results of the study stated that the fulfillment of the right to work for people with physical disabilities in Indonesia has not been effective with several challenges and criticisms, namely the Government has excluded disabled workers and there are still errors between ministries in solving problems of disabled workers.